Civics : government and economics in action - Davis, James E. 1940- 4 0 (James Edwin),16; 1933- Fernlund, Phyllis Maxey,;Woll, Peter; 5 Close Up Foundation (Needham, Massachusetts : Pearson/Premtice Hall, 2005)
... provides [a] current, and relevant look at the foundations of American government, citizenship, and the e American economic and legal systems--Amazon.
In association with Close Up Foundation.;Includes index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Civics;Political science -- Textbooks.;Textbooks.; Politics and government;Economic conditions;Politics and government;Economic conditions -- United States;United States;United States;United States -- Textbooks.;Textbooks.;Textbooks.;Textbooks.; 2